Electrochemical/Photochemical Aminations Based on Oxidative Cross-Coupling between C–H and N–H - Zhang, Heng; Lei, Aiwen (Synthesis, 2019)
The construction of nitrogen-containing molecules remains at the cutting edge of organic synthesis because of its wide application in various areas. Instead of prefunctionalized substrates, using free C–H and N–H bonds in the starting materials can supply a more sustainable avenue to the C–N bond-forming reactions. Compared with the well-developed transition-metal-catalyzed protocols, the strategy of introducing optical or electrical energy into reactions is fantastic and appealing. As a result, visible light or electricity mediated amination transformations have continued to develop over the past several years. In this short review, recent progress of carbon–nitrogen bond-forming reactions based on the oxidative cross coupling between C(sp2, sp3)–H and N–H are summarized.1 Introduction2 C(sp2)–H/N–H Oxidative Cross Coupling2.1 Aryl C(sp2)–H as C Nucleophiles2.1.1 Azoles as N Nucleophiles2.1.2 Sulfonamides or Sulfonimides as N Nucleophiles2.1.3 NH3 as N Nucleophile2.1.4 Morpholine as N Nucleophile2.1.5 Diaryl Amines as N Nucleophiles2.1.6 Primary Amines as N Nucleophiles2.1.7 Imides as N Nucleophiles2.1.8 Imines as N Nucleophiles2.2 Alkenyl C(sp2)–H as C Nucleophiles2.3 Aldehydic C(sp2)–H as C Nucleophiles3 C(sp3)–H/N–H Oxidative Cross Coupling3.1 Benzylic C(sp3)–H as C Nucleophiles3.2 α-C(sp3)–H as C Nucleophiles4 Conclusions and Outlook
Keywords: oxidative cross coupling; amination; C–H bond functionalization; electrochemistry; photochemistry